Comparison of teaching-learning behaviours in hands-on experiments and teacher-based demonstration chemistry laboratory sessions in Rwandan secondary schools - Pascal Kaneza; Jean Baptiste Nkurunziza; Innocent Twagilimana; Thumah Mapulanga; Anthony Bwalya (Cogent Education)
Hands-on experiments and teacher-based demonstrations are two standard teaching methods in secondary school when teaching chemistry in the laboratory. The available literature on these two teaching methods focuses on students’ academic achievement. Most of this literature reports inconsistent results, and few studies examined teachers’ and students’ behaviours occurring within laboratory setting. Therefore, this study explores five hands-on experiment and five teacher-based demonstrations laboratory sessions to examine students’ and teacher’s behaviours when learning/teaching solutions and titration. Students’ and teachers’ behaviours and the nature of verbal interactions were captured every 2 minutes of the laboratory sessions using the Laboratory Observation Protocol for Undergraduate STEM (LOPUS). The results revealed that students in the hands-on experiment laboratory and their teachers engaged more frequently in interactive behaviours, such as one-on-one dialogue, than their counterparts in the teacher demonstration laboratory. The results also indicated that two types of verbal interactions, including data analysis and calculations, equations and experimental procedures, and equipment/or laboratory techniques, were most frequent in the hands-on and teacher-based demonstration laboratories. However, the hands-on experiment laboratory showed a high percentage of verbal interactions. Therefore, chemistry teachers should prioritise hands-on experiments when teaching chemistry in the laboratory.